Prediction of Diamene-Based Chemosensors - Danil W. Boukhvalov; Vladimir Yu. Osipov (Chemosensors, 2022)
This paper presents the results of systematic studies of the atomic structure of the layered bulk, bilayer, and monolayer of diamene (a two-dimensional diamond monolayer recently synthesized by various methods) functionalized with fluorine and hydroxyl groups with the chemical formulas C2F and C2OH. The results of our calculations show that both types of diamene under discussion have a wide optical gap corresponding to the absorption of light in the UV spectral range. The formation of a boundary between these two types of diamene layers leads to a significant decrease in the band gap. Therefore, this layered material, with an interface between fluorinated and hydroxylated diamenes (C2F/C2OH structures), can be considered a suitable material for converting UV radiation into visible light in the orange-yellow part of the spectrum. The adsorption of acetone or water on the C2F/C2OH structures results in visible changes in the band gap. The effect on photoemission is different for different detected analytes. The presence of formaldehyde in water ensures the appearance of distinct peaks in the absorption spectra of structures based on C2F/C2OH. Our simulation results suggest that the simulated C2F/C2OH structures can be used as chemically stable, lightweight materials composed of common elements for a highly selective chemical sensor in liquid and air.